Lessons Learnt from the Nordics: How to Fight Long-term Unemployment - Erik Bjørsted; Elva Bova; Signe Dahl (Intereconomics, 2016)
This study examines policies that can successfully address long-term unemployment. It focuses on Denmark and Sweden, where, despite sizeable job losses during the crisis, labour market indicators are at present better than in any other EU country. By looking at the interaction between labour market flexibility (especially in hiring and firing regulations) and passive and active policies, we argue that well-designed active policies matter more than labour market flexibility for employment.
Keywords: 330; Arbeitsmarktpolitik; Langzeitarbeitslosigkeit; Arbeitsmarktflexibilität; Dänemark; Schweden